The bobcat (Lynx rufus) in the Nayarit Coastal Plain, México: presence, relative abundance and activity patterns - Luja, Víctor H.; Rodríguez-Estrella, Ricardo; Guzmán-Báez, Diana J.; Jiménez, Luis (Therya Notes, 2021)
The bobcat, Lynx rufus, is one of the six wild cats that inhabit México. It is distributed from sea level up to 3,600 m, occupying a wide variety of habitats including deserts, mountain ecosystems and wetlands. However, to date, there is no ecological information on the species in coastal wetlands. The general objective of this work is to provide the first ecological information systematically obtained on the bobcat in the Coastal Plain of Nayarit (NCP). We evaluated their historical and current presence, relative abundance, and activity patterns. We determined the historical presence of the bobcat in the NCP through a search of the words using the keywords “Lynx”, “rufus”, “lince”, “bobcat” and “Nayarit” in electronic databases. We implemented the protocol of the National Jaguar Census using camera traps in a 72 km2 area to document the bobcat’s presence, relative abundance, and activity patterns. Through the database search we find 23 bobcat’s records in area of at least 3,000 km2 of the NCP. From our fieldwork we obtained 30 independent records with a relative abundance of 1.28 bobcat photographs / 100 camera days. We documented the presence of at least 10 different individuals, including adults of both sexes, and possibly a pregnant female. Its activity is nocturnal; 40 % of the records occurred between 00:00 - 06:00 hr. The bobcat inhabits the coastal wetlands of Nayarit. The high values of relative abundance suggest a stable population in the NCP with respect to what has been reported in suitable habitats such as temperate forests and scrubs. Its nocturnal activity coincides with other studies on the species. Although, in general, the bobcat adapts well to disturbance generated by human activities, the impacts that these have on their populations in tropical wetlands are unknown. To ensure the permanence of the species, future work is recommended to know in depth its diet, reproduction, home range and genetic connectivity of this species in the tropical wetlands of western México.